(untitled) (Heidelberg, 2010)
The authors show that these violations are not isolated occurrences, but part of a paradigm shift. If companies want to stay successful in changing markets, they have to take a strategic approach to corporate finance. The authors use practical examples to demonstrate how this can be achieved. This book is intended not only for corporate finance experts, but also for students interested in the latest developments on the financial markets
Keywords: Corporations,Tập đoàn kinh tế